Depositional Conditions and Nature of Source Rocks of the Upper Part of the Balambo Formation in Northeastern Iraq Based on Rare Earth Elements Data - Al-Miamary, Falah Abed; Al-Lhaebi, Safwan Fathi; Al-Juboury, Ali Ismail; Swennen, Rudy (Iraqi Journal of Science, 2022)
The sequence in the upper part of the Balambo Formation is composed mainly of limestone alternating with marly limestones and dark grey shale in the Bosheen section (eastern Sulaymaniyah, northeastern Iraq) and has been studied in terms of its rare earth element (REE) content. The REEs are very low compared to modern marine sediments. They are depletion in LREEs, and enrichment in HREEs and (La/Yb)N in the studied rocks, indicating that these sediments retained the REEs pattern of marine waters. The negative Ce anomaly reflects direct sedimentation from marine waters under anoxic conditions with the contribution of terrigenous clays. The positive correlation of ∑REEs with Al, Ti, and Y, and the negative correlation of ∑REEs with CaO, in addition to the variation in Y/Ho ratio, all may indicate the presence of terrigenous fractions as the main source for REEs in the studied strata. The REEs pattern of the upper part of the Balambo Formation mostly shows original characteristics, some of which were modified by detrital input. According to (La/Yb)N ratios, the sedimentation rate varied during the deposition of the Balambo Formation in the function of its position along the continental margin.